1996
DOI: 10.1093/hmg/5.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Dramatically Different Phenotypes in Mouse Models of Human Tay-Sachs and Sandhoff Diseases

Abstract: We have generated mouse models of human Tay-Sachs and Sandhoff diseases by targeted disruption of the Hexa (alpha subunit) or Hexb (beta subunit) genes, respectively, encoding lysosomal beta-hexosaminidase A (structure, alpha) and B (structure, beta beta). Both mutant mice accumulate GM2 ganglioside in brain, much more so in Hexb -/- mice, and the latter also accumulate glycolipid GA2. Hexa -/- mice suffer no obvious behavioral or neurological deficit, while Hexb -/- mice develop a fatal neurodegenerative dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
169
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(178 citation statements)
references
References 39 publications
8
169
0
1
Order By: Relevance
“…20 Homozygous HEXB null mice (HEXBÀ/À) represent a reliable animal model of human Sandhoff disease and develop lysosomal storage bodies as well as a high rate of apoptosis Lysosomal storage suppresses ubiquitin pathway P Bifsha et al in neurons, microglia and Purkinje cells. 6 We found that UCH-L1 mRNA was reduced to about 30% in homozygous mutant mice (HEXBÀ/À) as compared to their wild-type siblings (HEXB þ / þ ).…”
Section: Resultsmentioning
confidence: 99%
“…20 Homozygous HEXB null mice (HEXBÀ/À) represent a reliable animal model of human Sandhoff disease and develop lysosomal storage bodies as well as a high rate of apoptosis Lysosomal storage suppresses ubiquitin pathway P Bifsha et al in neurons, microglia and Purkinje cells. 6 We found that UCH-L1 mRNA was reduced to about 30% in homozygous mutant mice (HEXBÀ/À) as compared to their wild-type siblings (HEXB þ / þ ).…”
Section: Resultsmentioning
confidence: 99%
“…2 One-month-old Hexb À/À mice were anesthetized with ketamine/xylazine (80 mg/ 4 mg/kg) and placed in a stereotaxic apparatus (David Kopf, Tujunga, CA, USA). Intracerebral injections were performed with the following coordinates: AP -1.5 mm, ML þ 2 mm, DV -3 mm.…”
Section: In Vivo Adhexb Administration In Hexb à/à Micementioning
confidence: 99%
“…1 The inability to treat the G M2 gangliosidoses has stimulated interest in the development of specific animal models, to enable experimentation with different approaches to therapy. To this end, we have constructed a mouse model of Sandhoff disease, by disruption of the murine Hexb gene, 2,3 in order to enable gene transfer experiments. Affected Hexb À/À mice display profound neurologic involvement and massive storage of G M2 ganglioside throughout the brain and spinal cord beginning at about 3 months with death 4-6 weeks later.…”
Section: Introductionmentioning
confidence: 99%
“…Two transgenic murine models of Sandhoff disease exist [23,25] that, like the human equivalent, exhibit premature death and display widespread neuronal storage of ganglioside, in addition to gliotic and inflammatory reactions and neuronal cell death [11,16,23,25,27]. The Sandhoff models have engendered much research directed at overcoming the challenges [1,2,4,11,14,15,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Sandhoff disease arises from defects in the gene encoding the β-subunit (hexb) of β-Nacetyl-d-hexosaminide N-acetylhexosaminohydrolase (EC 3.2.1.52) normally involved in the sequential catabolism of gangliosides and other glycoconjugates [11]. Sandhoff patients have widespread brain pathology which results in clinical symptoms including progressive mental and motor deterioration [10,11,21].Two transgenic murine models of Sandhoff disease exist [23,25] that, like the human equivalent, exhibit premature death and display widespread neuronal storage of ganglioside, in addition to gliotic and inflammatory reactions and neuronal cell death [11,16,23,25,27]. The Sandhoff models have engendered much research directed at overcoming the challenges [1,2,4,11,14,15,18,20].…”
mentioning
confidence: 99%